2002
DOI: 10.2746/042516402776767312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fibre type composition of gluteus medius and semitendinosus muscles of Dutch Warmblood foals and the effect of exercise during the first year postpartum

Abstract: Summary In order to obtain broader insights into the equine musculoskeletal system, we studied the fibre type composition of 2 locomotory muscles in biopsies from Dutch Warmblood foals taken at 3 different ages in the first year postpartum. The muscle fibre types were determined histochemically as well as immunohistochemically. ATPase‐characterised IIB fibres appear to express either IId or type IIa plus IId myosin heavy chain (MHC). A high percentage of fibres classified as IIA with ATPase expressed both fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 47 publications
1
8
0
2
Order By: Relevance
“…Nowadays this method is often used since a more detailed picture of the muscle and its adaptations to different kinds of stimuli can be obtained [10][11][12][13] . Nowadays this method is often used since a more detailed picture of the muscle and its adaptations to different kinds of stimuli can be obtained [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays this method is often used since a more detailed picture of the muscle and its adaptations to different kinds of stimuli can be obtained [10][11][12][13] . Nowadays this method is often used since a more detailed picture of the muscle and its adaptations to different kinds of stimuli can be obtained [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…O LD é o músculo epaxial mais superfi cial, sendo a atrofi a muito visível, enquanto que o GM, por ter também função postural, encontra-se em áreas mais profundas (DINGBOOM et al, 2002). Ainda, STUBBS et al (2010) relacionaram atrofi a destas musculaturas, com a ocorrência de cavalos com lombalgia.…”
Section: Resultsunclassified
“…Músculos do membro pélvico, como o Biceps Femoris e Semitendinosus, foram escolhidos por sua importante função na locomoção, sendo considerados músculos propulsivos (DINGBOOM et al, 2002). Estes músculos são caracterizados por terem grandes volumes e especializados em produzir muita força para realização do movimento (PAYNE et al, 2005).…”
Section: Resultsunclassified
“…It has been previously shown that muscle fibers with high oxidative potential have higher resistance and capacity for regeneration during and after exercise (Votion et al, 2007;Seene et al, 2008 and. Surveys have shown that age causes changes in muscle fiber types of MyHC isoform patterns and oxidative potential in horse skeletal muscle (Dingboom et al, 2002;Lehnhard et al, 2004). Horses older than 20 years had significantly less of type I and type IIA fibers in skeletal Leisson, Alev, Kaasik, Jaakma and Seene muscle and more of type IIx fibers than the young horses (Lehnhard et al, 2004;Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%